PENGARUH KOMPENSASI FINANSIAL DAN KOPENSASI NON FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN - Jaenab Jaenab (Universitas Mahendradatta Denpasar, 2021)
This study aims to explain the effect of variable financial compensation and non-financial compensation on employee job satisfaction simultaneously and partially. This study uses an explanatory research method with a quantitative approach. The population in this study were 36 employees and the research sample used was a saturated sample of 36 employees at PT. Kawi brilliant Bima. The analysis used is multiple linear regression. The results of the study simultaneously show that financial compensation and non-financial compensation have a significant effect on employee job satisfaction. Sig value. The F which is obtained is 0,000. The results of the study partially show that financial compensation has no significant effect on employee job satisfaction with a sig value. t of -283. The result of the research is partially known that non-financial compensation has a significant effect on employee job satisfaction with a sig.t value of 5,563